Implementasi Metode Ummi Pada Pembelajaran Al-Qur’an di SMA Al-Muhajirin - Muhamad Fauzi; Dedih Surana; Arif Hakim (UNISBA Press, 2025)
Abstract. The Umi method as the main material in compiling this work is reviewed from the aspects of the process and results as well as the advantages and disadvantages. The author chose qualitative as the basic method to complete the compilation of the Work which is obtained through documentation, interviews and observations. The objects are teachers, students and principals and several other sources. The results of this work are that in Al Muhajirin High School this method has been implemented for 13 years and has proven effective in improving students' skills in reading the Qur'an. In the process, teachers have very urgent duties and functions starting from preparing materials, such as tajwid and ghorib, and creating an organized and interesting learning experience. Students show high enthusiasm in learning, which strengthens their connection with the Islamic community. Observations show that teacher creativity in teaching is a key factor in the success of this method. The Ummi method is recommended for application in other educational environments because it has been proven to be able to improve understanding of the Qur'an effectively. Keywords: Al-Muhajirin High School, Educational Effectiveness, Qur'an Learning, Ummi Method Abstrak. Metode Umi sebagai bahan utama dalam penyusunan karya ini ditelaah dari aspek proses dan hasil serta kelebihan dan kekurangan. Penulis memilih kualitatif sebagai metode dasar untuk menyelesaikan penyusunan Karya yang mana di dalamnya untuk memperolehnya melalui dokumentasi, wawancara dan observasi. Objeknya yaitu guru komahasiswa dan kepala sekolah serta beberapa narasumber lain. Hasil karya ini bahwa di SMA Al Muhajirin metode ini sudah diimplementasikan selama 13 tahun dan terbukti efektif dalam rangka meningkatkan skill siswa aspek membaca Alquran. Dalam prosesnya guru memiliki tupoksi yang sangat urgent yang dimulai dari mempersiapkan materi, seperti tajwid dan ghorib, serta menciptakan pengalaman belajar yang terorganisir dan menarik. Siswa menunjukkan antusiasme tinggi dalam belajar, yang memperkuat keterhubungan mereka dengan komunitas Islami. Observasi menunjukkan bahwa kreativitas guru dalam mengajar menjadi faktor kunci keberhasilan metode ini. Metode Ummi direkomendasikan untuk diterapkan di lingkungan pendidikan lain karena terbukti mampu meningkatkan pemahaman Al-Qur'an secara efektif. Kata Kunci: Efektivitas Pendidikan, Metode Ummi, Pembelajaran Al-Qur'an, SMA Al-Muhajirin